To factor 9z + 18 with the greatest common factor (GCF), you need to find the largest common factor of both terms. In this case, the GCF is 9.
First, divide each term by the GCF:
9z ÷ 9 = z
18 ÷ 9 = 2
Now, rewrite the expression using the divided terms:
9z + 18 = 9(z + 2)
So, the factored form of 9z + 18 with the GCF is 9(z + 2).
factor 9z + 18 with gcf
I don't really know how to do it
3 answers
factor 16d - 12 usin gcf
To factor 16d - 12 using the greatest common factor (GCF), we need to find the largest common factor of both terms. In this case, the GCF is 4.
First, divide each term by the GCF:
16d ÷ 4 = 4d
-12 ÷ 4 = -3
Now, rewrite the expression using the divided terms:
16d - 12 = 4(4d - 3)
So, the factored form of 16d - 12 with the GCF is 4(4d - 3).
First, divide each term by the GCF:
16d ÷ 4 = 4d
-12 ÷ 4 = -3
Now, rewrite the expression using the divided terms:
16d - 12 = 4(4d - 3)
So, the factored form of 16d - 12 with the GCF is 4(4d - 3).